2021
DOI: 10.1177/1470320321995074
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin converting enzyme gene polymorphism and essential hypertension: A systematic review and meta-analysis

Abstract: Background: The current meta-analytic study explored the relation between ACE gene insertion/deletion (I/D), and the risk of EH by reviewing relevant trials so as to determine the association between Angiotensin Converting Enzyme (ACE) gene polymorphism and essential hypertension (EH) susceptibility. Methods: Relevant studies published before May 2019 were collected from the PubMed, Cochrane, Embase, CNKI, VANFUN, and VIP databases. Results: Fifty-seven studies involving a total of 32,862 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
16
0
3
Order By: Relevance
“…On the other hand, prior to the COVID-19 pandemic, association studies between the ACE genotype and arterial hypertension and type 2 diabetes mellitus were published. A meta-analysis found an association between the D allele and essential hypertension in Asian and Caucasian population [25]. Another meta-analysis found that the D variant was associated with a 14% increased risk of type 2 diabetes mellitus relative to the I variant, in Caucasian and East Asians [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prior to the COVID-19 pandemic, association studies between the ACE genotype and arterial hypertension and type 2 diabetes mellitus were published. A meta-analysis found an association between the D allele and essential hypertension in Asian and Caucasian population [25]. Another meta-analysis found that the D variant was associated with a 14% increased risk of type 2 diabetes mellitus relative to the I variant, in Caucasian and East Asians [26].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of ACE1 I/D rs1799752 polymorphism with the risk of various diseases has been studied previously. It was demonstrated that I/D variant can impose the risk of hypertension in African ethnicity (Mengesha et al, 2019 ), type 2 diabetes (T2DM) in Caucasian and East‐Asian ethnicities (Zhou et al, 2010 ), and both hypertension and T2DM in Caucasian and Asian ethnicities (Liu et al, 2021 ), and chronic kidney disease in Asian hypertensive male patients (Lin et al, 2014 ) which are thought to get worsen during COVID‐19 (Matta et al, 2020 ). During the COVID‐19 pandemic, the role of this variant in the severity had also investigated by different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk factors of HF are not fully recognized yet, and the genetic determinants of cardiac function are probable contributors. There are several reports that genetic variations in the RAS play important roles in the development of CAD, HT, LVH, or cardiomyopathy [ 6 , 7 ]. The key components of the RAS are angiotensinogen (AGT), angiotensin converting enzyme (ACE), and angiotensin II Type 1 receptor (AGTR1).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports that genetic variations in the RAS play important roles in the development of CAD, HT, LVH, or cardiomyopathy [6,7]. The key components of the RAS are angiotensinogen (AGT), angiotensin converting enzyme (ACE), and angiotensin II Type 1 receptor (AGTR1).…”
Section: Introductionmentioning
confidence: 99%